Understanding common errors in solving math problems on systems of linear equations with two variables: A study of 8th grade students - Octaviana Koten; Fitria Sulistyowati; Muhammad Ghozian Kafi Ahsan; K. S. Kuncoro (Universitas Sarjanawiyata Tamansiswa, 2023)
This study aimed to identify the types of mistakes students made in solving SPLDV problems based on the Kastolan technique and why they made these mistakes. This study used a descriptive qualitative approach which was carried out at SMP Negeri 4 Sewon. The research subjects were 2 students of eighth grade who were selected based on the completeness of the answers and the answers were then examined and analyzed. Data was collected using documentation, interviews, observations, and tests. The instruments used were observation sheets, tests, unstructured interview guidelines. The data were then analyzed descriptively. The results of this study are that there are two categories of errors that are mostly made by students when solving SPLDV problems, namely conceptual and technical errors. This research is expected to be a reference for further research related to errors in solving SPLDV problems.